Design of Dual Inhibitors of Soluble Epoxide Hydrolase and LTA(4) Hydrolase - Hiesinger, Kerstin (ACS Med Chem Lett, 2019)
[Image: see text] Multitarget anti-inflammatory drugs interfering with the arachidonic acid cascade exhibit superior efficacy. In this study, a prototype dual inhibitor of soluble epoxide hydrolase (sEH) and LTA(4) hydrolase (LTA(4)H) with submicromolar activity toward both targets has been designed and synthesized. Preliminary structure–activity relationship studies were performed to identify optimal substitution patterns. X-ray structure analysis of a promising dual inhibitor in complex with sEH, as well as molecular docking with LTA(4)H provided a rationale for further optimization. Hereby, scaffold extension was successfully applied to yield potent dual sEH/LTA(4)H inhibitors. The spectrum of pro- and anti-inflammatory lipid mediators was evaluated in M1 and M2 macrophages, stimulated with LPS, and incubated with the most promising compound 14. The effect of 14 on the inflammatory lipid mediator profile characterizes dual sEH/LTA(4)H inhibitors as an interesting option for future anti-inflammatory agent investigations.